PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, CITA RASA, DAN BRAND IMAGE TERHADAP LOYALITAS PELANGGAN PDA RUMAH MAKAN BEBEK SINJAY BANGKALAN - Yahya Abdul Manaf; Estik Hari Prastiwi (Cahaya Ilmu Bangsa, 2024)
This research examines the influence of Product Quality, Price Perception, Taste, and Brand Image on Customer Loyalty at Bebek Sinjay Bangkalan Restaurant. The population is customers who have purchased more than once. Using quantitative data, purposive sampling technique with 100 respondents, and questionnaires as data collection methods, analysis was carried out using multiple linear regression, t test (partial), and F test (simultaneous). The research results state that simultaneously (F Test), Product Quality (X1), Price Perception (X2), Taste (X3), and Brand Image (X4) have a significant effect on Customer Loyalty (Y), with F count 53.326 > F table 2,467. Partially (t test), Product Quality (X1) and Taste (X3) have a significant influence on Customer Loyalty, with significant values ​​of 0.018 and 0.001 < 0.05 respectively. Brand Image (X4) is also significant with a value of 0.001 < 0.05, while Price Perception (X2) is not significant with a value of 0.577 > 0.05.